Reducing Dietary Sodium Intake among Young Adults in Ghana: A Call to Action - Peprah, E.; Laar, A.; Commodore-Mensah, Y.; et al (www.mdpi.com/journal/nutrients, 2023)
The positive association between excessive dietary sodium intake, hypertension, and cardiovascular disease (CVD) has been widely investigated in observational studies and clinical trials. Reducing sodium intake is a proven strategy to prevent hypertension and the onset of CVD, a major cause of morbidity and mortality globally. Africa has the youngest population globally, which is key to the continent’s sustainable development. However, in Africa, the epidemics of hypertension and CVD negatively impact life expectancy and economic growth. Ghana, like other African countries, is no exception. The factors contributing to the increasing burden of CVD and excessive sodium consumption are multi-faceted and multi-level, including individual lifestyle, neighborhood and built environments, and socio-economic and health policies. Thus, the implementation of evidencebased interventions such as the World Health Organization Best Buys that target the multi-level determinants of sodium consumption is urgently needed in Ghana and other African countries. The aim of this commentary is to highlight factors that contribute to excessive sodium consumption. Second, the commentary will showcase lessons of successful implementation of sodium reduction interventions in other countries. Such lessons may help avert CVD in young adults in Ghana and Africa.
Research Article
Keywords: evidence-based interventions; global health; implementation research; sodium intake